Synergistic Effects of BAY 60‐4552 and Vardenafil on Relaxation of Corpus Cavernosum Tissue of Patients with Erectile Dysfunction and Clinical Phosphodiesterase Type 5 Inhibitor Failure. (19th February 2013) - Albersen, Maarten; Linsen, Loes; Tinel, Hanna; Sandner, Peter; Van, Koenraad
Abstract Introduction. Overall efficacy rates of phosphodiesterase type 5 inhibitors (PDE5‐i) for erectile dysfunction (ED) are 60–70%. PDE5‐i treatment failures currently have to resort to invasive treatment options for restoration of erectile function. Aims. To assess changes in the nitric oxide (NO)/cyclic guanosine monophosphate (cGMP)/protein kinase (PKG) pathway in human corpus cavernosum (HCC) of PDE5‐i nonresponders compared with healthy controls. To evaluate the effects of BAY 60‐4552, a stimulator of soluble guanylate cyclase (sGC), and vardenafil on relaxation of HCC strips from PDE5‐i nonresponders. Main Outcome Measures. mRNA expression, morphological localization of the NO/cGMP/PKG pathway, and relaxant capacity of both compounds alone or combined. Analysis of variance, t‐test or Mann–Whitney test based upon number of groups and normality of data. Methods. HCC tissues were harvested after consent from individuals undergoing penile prosthesis implantation (patients) and potent patients undergoing transurethral surgery (healthy controls, needle biopsy). HCC tissues of patients were compared with those of healthy controls for the expression of mRNA coding for PDE5A, eNOS, PKGα1, PKG2, sGCα1, sGCα2, sGCβ1, sGCβ2, α‐smooth muscle actin (aSMA) and β‐actin by quantitative polymerase chain reaction (qPCR). The respective proteins were localized using immunofluorescence. Tissue strips of patients were precontracted with phenylepinephrine followed by incubation with 1 μM of either vardenafil or BAY 60‐4552, or both simultaneously. Results. The main targets in the NO/cGMP/sGC pathway were downregulated in PDE5‐i nonresponders. The pathway was morphologically located to HCC smooth muscle, of which the overall content was preserved in ED patients based on aSMA expression. BAY 60‐4552 and vardenafil have synergistic effects on relaxation of HCC of PDE5‐i nonresponders. The main limitation is the small amount of control tissue precluding functional testing on these samples. Conclusion. Despite downregulation of the NO/cGMP/PKG pathway, combining BAY 60‐4552 with vardenafil significantly enhanced relaxation HCC strips of PDE5‐i nonresponders.